2001
DOI: 10.1108/09578230110386214
|View full text |Cite
|
Sign up to set email alerts
|

Assessing leadership potential: fast track to school leadership

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Currently, the topic of project management is not included in their introductory training. This omission is highlighted in studies focusing on new school leaders (Elsner and Bednarek, 2010;Pisoňová, 2011;Tolinson and Holmes, 2001) and in those dealing with the content of school management training (Eger, 2006;Everard et al, 2004). Buganza et al (2013) showed a direct positive link between education in project management and the subsequent behaviour of graduates of such training courses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Currently, the topic of project management is not included in their introductory training. This omission is highlighted in studies focusing on new school leaders (Elsner and Bednarek, 2010;Pisoňová, 2011;Tolinson and Holmes, 2001) and in those dealing with the content of school management training (Eger, 2006;Everard et al, 2004). Buganza et al (2013) showed a direct positive link between education in project management and the subsequent behaviour of graduates of such training courses.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, the topic of project management is not included in their introductory training. This omission is highlighted in studies focusing on new school leaders (Elsner and Bednarek, 2010; Pisoňová, 2011; Tolinson and Holmes, 2001) and in those dealing with the content of school management training (Eger, 2006; Everard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Formally and informally recruiting teachers to join the school principal workforce can involve contest mobility where each candidate's success depends on his or her merits as assessed in competitive but closed-door processes or sponsored mobility under which certain teachers are recruited for an accelerated pathway to the principalship (Tomlinson and Holmes, 2001). Gooden and Gonzales (2012) describe a university preparation programme in the United States that begins by asking local district leaders to nominate individuals who have purportedly exhibited a set of desirable leadership experiences and commitments as well as inviting local teachers interested in the principalship.…”
Section: Complementary Dimensions To Examine Pathways To the Principa...mentioning
confidence: 99%
“…To the extent that someone in a position of power decides who ‘looks/acts’ and does not ‘look/act’ like a principal in the making, formal and informal sponsorship present potential for inequitable access based on candidates’ race, gender, religious affiliation, among others (Davis and Bowers, 2019; Miller, 2014). Understanding how, across different countries, gatekeepers recognize and tap prospective principals, what are the characteristics considered desirable as well as how culture and policies shape these practices, can reveal how inequities in access are interrupted as well as perpetuated (Tomlinson and Holmes, 2001).…”
Section: Conclusion and Topics For Further Researchmentioning
confidence: 99%
“…The issue of fast‐tracking and accelerated leadership development has been well explored (e.g. Tomlinson and Holmes, 2001; Koontz, 2004). But fast‐tracking often encounters the issue of unmet expectations (Krishnan and Varrkey, 2004) where an individual or cohort has undergone development, but their organization may not be able to put them into a position where they can explore and use their new‐found skills and competencies.…”
Section: Introduction and Aimsmentioning
confidence: 99%